A Comprehensive Analysis of How to Improve Patient Outcomes Through Multidisciplinary Collaboration - Alshanqiti, Walaa Abdullah; Alerfan, Khalid Hussien Humeyr; Alalawi, Ahmed Mohammed; Alshomrani, Mohammed Ahmed; Muqaybil , Maram Jameel; Almarwani, Amal Mutlag Hassan; Alzubidi, Nada Abdullah; Albiah, Ali Khalil; Mahneshi, Ali Mohammed Ali; Alshamrani, Samer Ahmed (Journal of Ecohumanism, 2024)
Enhancing patient satisfaction/therapeutic outcomes is still one of the significant aims of healthcare organizations, and more so with the emergence of advanced patient needs. Of the studied strategies, one with the most potential for improving outcomes is the MDC concept of healthcare professionals’ functions, which implies the involvement of specialists of different disciplines in comprehensively oriented care. This paper aims to identify the gaps in knowledge on how MDC could enhance patient care by reviewing the literature and analyzing data sources. However, they were often prescriptive in their offerings by focusing on integrated care, shared decision-making, and communication. Also, the research focuses on the potential issues encountered in teamwork and how these issues can be resolved. Using this lens, we hope to offer policy-relevant findings about how MDTs are contributing to enhancing the delivery of health care and client consequences.